2023
DOI: 10.21203/rs.3.rs-3222611/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell autonomous role of border associated macrophages in ApoE4 neurovascular dysfunction and susceptibility to white matter injury

Abstract: Apolipoprotein-E4 (ApoE4), the strongest genetic risk factor for sporadic Alzheimer’s disease, is also a risk factor for microvascular pathologies leading to cognitive impairment, particularly subcortical white matter injury. These effects have been attributed to alterations in the regulation of the brain blood supply, but the cellular source of ApoE4 and the underlying mechanisms remain unclear. In mice expressing human ApoE3 or ApoE4 we report that border associated macrophages (BAM), myeloid cells closely a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…We were also interested in targeting of border-associated macrophages as they are key players in a myriad of CNS disorders, including driving neurovascular dysfunction in hypertension and Alzheimer’s disease. 53,54 One recent study identified two subtypes of macrophages, Lyve1+ and MHCII+, and demonstrated that Lyve1+ macrophages decrease with age leading to impaired CSF dynamics that can be restored with administration of macrophage colony-stimulating factor (M-CSF). 42 MHCII+ BAMs are also implicated in neurodegeneration, for example by initiating α-synuclein-mediated neuroinflammatory responses through restimulation of CD4+ T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…We were also interested in targeting of border-associated macrophages as they are key players in a myriad of CNS disorders, including driving neurovascular dysfunction in hypertension and Alzheimer’s disease. 53,54 One recent study identified two subtypes of macrophages, Lyve1+ and MHCII+, and demonstrated that Lyve1+ macrophages decrease with age leading to impaired CSF dynamics that can be restored with administration of macrophage colony-stimulating factor (M-CSF). 42 MHCII+ BAMs are also implicated in neurodegeneration, for example by initiating α-synuclein-mediated neuroinflammatory responses through restimulation of CD4+ T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…New studies in mouse models suggest APOE ε4 driven neurovascular uncoupling, with APOE ε3/ε4 mice and APOE ε4/ε4 mice showing differential cerebral perfusion and glucose uptake ( Onos et al, 2023 ). Further, boarder association macrophages (BAMs) have been shown to provide APOE ε4 to a detrimental effect to the neurovascular unit ( Iadecola et al, 2023 ). When APOE is knocked out of BAM cells specifically, function of the neurovascular unit is rescued, providing another cell type and mechanism by which APOE regulates NVU integrity.…”
Section: Three Mechanisms By Which Apoe ε4 Increas...mentioning
confidence: 99%